2014
DOI: 10.1021/om500329q
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Hydrogenation Activity of Iron Dialkyl Complexes with Chiral Bidentate Phosphines

Abstract: The activity of bis(phosphine) iron dialkyl complexes for the asymmetric hydrogenation of alkenes has been evaluated. High-throughput experimentation was used to identify suitable iron−phosphine combinations using the displacement of pyridine from py 2 Fe(CH 2 SiMe 3 ) 2 for precatalyst formation. Preparative-scale synthesis of a family of bis(phosphine) iron dialkyl complexes was also achieved using both ligand substitution and salt metathesis methods. Each of the isolated organometallic iron complexes was es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 79 publications
1
36
0
1
Order By: Relevance
“…There is some experimental proof on the in situ transformation of organometallic compounds into metal nanoparticles, which can work as the active sites for hydrogenation reactions. 294 In a recent work, Gieshoff et al have isolated series of subnanometric Fe clusters (Fe 4 , Fe 6 , and Fe 7 ) from the reaction mixture when using mononuclear Fe compound as the precatalyst in the presence of ligands for hydrogenation of alkenes. 295 Kinetic studies and structural analysis showed that those subnanometric Fe clusters were more efficient than Fe nanoparticles and were able to perform hydrogenation of alkenes under very mild conditions (1–4 bar of H 2 at 20 °C), being promising substitutes for noble metal catalysts.…”
Section: Catalytic Applications Of Metal Nanoclustersmentioning
confidence: 99%
“…There is some experimental proof on the in situ transformation of organometallic compounds into metal nanoparticles, which can work as the active sites for hydrogenation reactions. 294 In a recent work, Gieshoff et al have isolated series of subnanometric Fe clusters (Fe 4 , Fe 6 , and Fe 7 ) from the reaction mixture when using mononuclear Fe compound as the precatalyst in the presence of ligands for hydrogenation of alkenes. 295 Kinetic studies and structural analysis showed that those subnanometric Fe clusters were more efficient than Fe nanoparticles and were able to perform hydrogenation of alkenes under very mild conditions (1–4 bar of H 2 at 20 °C), being promising substitutes for noble metal catalysts.…”
Section: Catalytic Applications Of Metal Nanoclustersmentioning
confidence: 99%
“…In particular, Fe appears to be the most appealing base metal due to its abundance (5 % of Earth's crust), low cost and scarce toxicity 3. In spite of these attractive features, the application of Fe in AH is still very limited:4 a few chiral catalysts have been developed for the hydrogenation of ketones5 and ketoimines,5b,6 while no examples were reported with olefins 7…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, understanding and controlling ligand coordination and dissociation equilibria are key to enabling catalyst stability and communicating stereochemical information. Unlike other tactics for improving catalyst performance, rational control of catalyst activation and deactivation are challenging and often circumvented by increased catalyst loadings (9)(10)(11). With classic transition metal catalysts such as Wilkinson's (Ph 3 P) 3 RhCl (12) and (Ph 3 P) 3 RuCl 2 (13) (Ph, phenyl), catalyst activation and, ultimately, performance is limited by phosphine dissociation equilibria and halide coordination ( Fig.…”
mentioning
confidence: 99%